Employment effects of an emergency assistance package for migrants displaced by COVID-19 in India - Varshney, Deepak; Meenakshi, J. V. (Wiley, 2023)
This paper examines the employment effects of an emergency assistance package by the Indian government, the Garib Kalyan Rozgar Abhiyaan that had the sole objective of providing employment to returning migrants. It was targeted to 116 districts that had seen returning migrants in excess of 25,000, was limited in duration to 4 months, and was directed at top-up funding to public works and 25 other target sectors in rural areas. Using a sharp RD approach, we find that the intervention had substantive impacts on employment and in reducing rationing in public works and that it did so in a cost-effective manner. In contrast to the widespread impression of a slow-moving bureaucracy, these results point to an administrative machinery that was able to successfully implement this project within a relatively short period of time.